Manajemen Pemasaran Sekolah: Membangun Citra dan Menarik Siswa Potensial - Hasanah, Amalia; Bahrany Hafis, Rafly; Rifqi Syahlan, Nawfal; Kusumaningrum, Hesti (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2025)
As time goes by, society is now continuing to develop by choosing quality educational institutions and being able to create intelligent and quality generations. So it is important for schools to promote their schools well. Or known as School Marketing Management. To capture interest and become an attraction of education, one of them is the image of the school. Because the image of the school will be a consideration for parents to send their children to school. The research method uses the library research method. To find information related to the theme, namely School Marketing Management: Building Image and Attracting Potential Students. The search results show that Marketing Management is planning, directing, and supervising all marketing activities of the company or part of marketing. If associated with the world of schools or education, it is a process that must be carried out by schools or madrasas to provide satisfaction to stakeholders and the community. Which aims to know and understand customer needs and be able to provide services that are in accordance with customer needs. To form a good image in an Educational Institution, schools must know how to do promotions well that are effective and efficient. But before that, every school must ensure that there are 8 things that the school must have. So if these 8 things have been met, it will make it easier to market the school.